Facilitating Interaction: Board Games as Social Lubricants in the Ancient Near East. Issue 2 (May 2016) - Crist, Walter; de Voogt, Alex; Dunn‐Vaturi, Anne‐Elizabeth
Summary: This re‐evaluation of existing data on board games from the Near Eastern Bronze Age demonstrates their function as social lubricants in cross‐cultural interaction. Board games are situated theoretically as liminoid practices, which lie outside the bounds of normative social behaviour and allow for interaction across social boundaries. Utilizing double‐sided game boards, with an indigenous game on one side and a newly introduced game on the other, the games of senet, mehen and twenty squares provide evidence for social interactions. Cypriots had adopted Egyptian mehen and senet by the third millennium BC, and indigenized the games. This lies in contrast to the game of twenty squares, which had a particular role among elites in the Late Bronze Age interaction sphere. This anthropological discussion of evidence relating to gaming seeks to inspire further research on the role of board games in society.